PHYTOCHROME AND FLOWERING TIME1/MEDIATOR25 Regulates Lateral Root Formation via Auxin Signaling in Arabidopsis - Raya-González, Javier (American Society of Plant Biologists, 2014)
Root system architecture is a major determinant of water and nutrient acquisition as well as stress tolerance in plants. The Mediator complex is a conserved multiprotein complex that acts as a universal adaptor between transcription factors and the RNA polymerase II. In this article, we characterize possible roles of the MEDIATOR8 (MED8) and MED25 subunits of the plant Mediator complex in the regulation of root system architecture in Arabidopsis (Arabidopsis thaliana). We found that loss-of-function mutations in PHYTOCHROME AND FLOWERING TIME1 (PFT1)/MED25 increase primary and lateral root growth as well as lateral and adventitious root formation. In contrast, PFT1/MED25 overexpression reduces these responses, suggesting that PFT1/MED25 is an important element of meristematic cell proliferation and cell size control in both lateral and primary roots. PFT1/MED25 negatively regulates auxin transport and response gene expression in most parts of the plant, as evidenced by increased and decreased expression of the auxin-related reporters PIN-FORMED1 (PIN1)::PIN1::GFP (for green fluorescent protein), DR5:GFP, DR5:uidA, and BA3:uidA in pft1-2 mutants and in 35S:PFT1 seedlings, respectively. No alterations in endogenous auxin levels could be found in pft1-2 mutants or in 35S:PFT1-overexpressing seedlings. However, detailed analyses of DR5:GFP and DR5:uidA activity in wild-type, pft1-2, and 35S:PFT1 seedlings in response to indole-3-acetic acid, naphthaleneacetic acid, and the polar auxin transport inhibitor 1-N-naphthylphthalamic acid indicated that PFT1/MED25 principally regulates auxin transport and response. These results provide compelling evidence for a new role for PFT1/MED25 as an important transcriptional regulator of root system architecture through auxin-related mechanisms in Arabidopsis.